Estratégias de produção e influências na cadeia de suprimentos: estudos de caso no setor de linha branca - Diniz, Camila Oficiati (Universidade Federal de São Carlos, 2010)
The competitive environment of the XXI century subjects corporations to some major challenges. The complexity of relationships as more and more multinational companies merge and interaction between companies increases, has opened up the way for organizations to recognize the strategic role played by the production area. The management of these relationships is appearing more and more frequently on meeting agendas of high level leadership of organizations. In terms of this, the objective of this research is to analyze the influence between links, central company and suppliers, who belong to a cross-section of the supply chain of white goods, based on the theories of production strategy and the supply chain management. The field research was conducted as a qualitative exploratory survey, by means of three case studies in three companies, these being a factory of white goods (central company) and two tier one suppliers. The main method used to obtain the information was actually visiting the companies and conducting interviews with their managers. The main conclusion from this study is that there is a strong connection (influence) of competitive strategy and production strategy of the central company on the strategies and structural and infrastructural decisions of the analyzed suppliers, being that this influence is becoming more powerful through the buying power of the central company and through threats from new competitors, mainly Asian suppliers.
Keywords: Cadeia de suprimentos; Estratégia de produção; Indústria de linha branca; Industrial strategy; Supply chain; Home appliance; White goods; ENGENHARIAS::ENGENHARIA DE PRODUCAO